2008
DOI: 10.4049/jimmunol.181.9.6061
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Frizzled-Related Protein 1 Is Estrogen Inducible in Bone Marrow Stromal Cells and Suppresses the Earliest Events in Lymphopoiesis

Abstract: It has long been known that lymphopoiesis is transiently suppressed during pregnancy, which can be experimentally simulated by estrogen treatment. We now confirm with Rag1/GFP reporter mice that early lymphoid progenitors in the lineage marker− c-kithigh ScaI+, hematopoietic stem cell-enriched fraction of bone marrow are particularly depressed in these circumstances. Hematopoietic and environmental cells are both potential hormone targets and, because of this complexity, very little is known regarding mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 72 publications
2
44
0
Order By: Relevance
“…43 Previous studies showed that SFRP1 can modulate canonical and noncanonical Wnt signaling both positively and negatively. [44][45][46][47] Here, we demonstrated that SFRP1 selectively inhibited the canonical pathway in t(8;21)-leukemia cells. This observation was also supported by significant down-regulation of canonical Wnt/␤-catenin target genes (CCND1 and MYC) but not noncanonical Wnt targets (PCDH8, JUN, ATF2, and SUZ12) 34,44,48 in Kasumi-1 cells after SFRP1 treatment.…”
mentioning
confidence: 60%
“…43 Previous studies showed that SFRP1 can modulate canonical and noncanonical Wnt signaling both positively and negatively. [44][45][46][47] Here, we demonstrated that SFRP1 selectively inhibited the canonical pathway in t(8;21)-leukemia cells. This observation was also supported by significant down-regulation of canonical Wnt/␤-catenin target genes (CCND1 and MYC) but not noncanonical Wnt targets (PCDH8, JUN, ATF2, and SUZ12) 34,44,48 in Kasumi-1 cells after SFRP1 treatment.…”
mentioning
confidence: 60%
“…This alternative view offers a possible explanation for previous results showing that Sfrp1 is required for positive regulation of -catenin in, for example, hematopoietic progenitors (Renstrom et al, 2009;Yokota et al, 2008). RESEARCH REPORT Sfrp in Wnt signalling activation …”
Section: Research Reportmentioning
confidence: 78%
“…One possibility was that DC precursors in ER␣ Ϫ/Ϫ mice are defective due to the absence of factors supplied by estrogen-responsive BM stromal cells in vivo. 29 To determine whether the effect of ER␣ signaling on IRF4 expression was intrinsic to hematopoietic DC precursors, we generated ER␣ ϩ /ER␣ Ϫ/Ϫ mixed BM chimeric mice, and BM cells from these chimeric mice were placed into GM-CSF-driven cultures. After 7 days, ER␣ ϩ cells expressed higher amounts of IRF4 and had developed into both CD11b hi and CD11b int DC subsets, whereas ER␣ Ϫ/Ϫ cells expressed lower amounts of IRF4 and had developed primarily into CD11b hi DCs ( Figure 5E,F).…”
Section: Er␣ Signaling In Hematopoietic Cells Increases Irf4 Expressimentioning
confidence: 99%